Numerical results and stability of ADI method to two-dimensional advection-diffusion equations with half step of time (Jurusan Matematika FMIPA UNNES, 2022)
We are concerned with the study of stability and numerical results of discretization for alternating direct implicit (ADI) method to two-dimensional advection-diffusion equation. We first discrete two-dimensional advection-diffusion by using forward difference of time and central difference of space. Then, we have two matrices with the step size of time and , in which this technique is the idea of ADI method. The stability is established by using the Von-Neumann stability technique where the stability characteristic of ADI method is unconditionally stable.